Multinucleon transfer reactions: a mini-review of recent advances - Mijatović, Tea (Frontiers in Physics, 2022)
Multinucleon transfer reactions, characterized by the exchange of many nucleons at energies in the vicinity of the Coulomb barrier, have been extensively used in the last decades to understand the production of neutron-rich nuclei, as well as to study their structure. In this Mini Review, recent results related to the production mechanism of heavy neutron-rich nuclei obtained with stable and radioactive beams will be discussed together with the results concerning the proton transfer channels. Additionally, newest results from a series of experiments carried out to study nucleon-nucleon correlations for closed-shell and superfluid systems employing the large solid angle magnetic spectrometer PRISMA will be summarized.